Knee prosthesis sizes in Indian patients undergoing total knee replacement - Jain, Jagdish Prasad (International Surgery Journal, 2016)
Background:Various studies have shown the ethnic difference for anthropometric measurements for Asian population compared to western world. The current available knee implants does not address the ethnic differences in the knee sizes. There is a paucity of clinical data published from India. Methods:This was a retrospective study in 1228 knees underwent total knee replacement between years 2008 to 2012. The parameters analyzed in this study were age and sex wise distribution and mismatch analysis for femoral and tibial component of the implants. Results:Out of total 1228 knees operated, 477 were in male and 751 in female patients. The most commonly used femoral implant size was 2.5 in males (34.6%, n=165) and size 2.0 in females (47.1%, n=165). The tibial implant Size 3.0 in males (53.3%, n=254) and size 2.0 in females (54.4%, n=409) was used frequently. In mismatch analysis, we found that tibial component was larger than femoral in 49.7% of cases (n=610), equal in 46.3% (n=569) and smaller in 4% (n=49) of cases operated. Conclusions:Higher aspect ratio and splaying of the lower end femur needs to be considered to meet the knee prosthesis size for of Indian population. This study may give the new insights to the specific implant designs for Indian patients.